Pasar 16 Ilir: Ruang Perdagangan di Kota Palembang Awal Abad 20 - Farida R. Wargadalem; Helen Susanti (Universitas Negeri Padang, 2023)
This research is based on the lack of narrative regarding the market as an important space for trade in the Palembang City area. In fact, the market is one of the most important trading spaces in the transaction process, meeting sellers and buyers, and cultural exchange. Palembang as a trading city has a fairly well-known market, especially during the Dutch colonial period, namely the Pasar 16 Ilir Palembang area. Merchants from various ethnic backgrounds trade at Pasar 16 Ilir, such as: Local traders from the Archipelago, Arabs, India, China, to Europe. This study aims to reveal the role of Pasar 16 Ilir as a trading space in the Palembang region. This research uses historical methods by utilizing a variety of literature, such as: archives, journals, and books. The results of this study indicate that the Pasar 16 Ilir area began to form in 1900 (early 20th century). The market became lively and growing because of its strategic location on the outskirts of the Musi River and the development being carried out by the colonialists. New, more modern stalls were built to replace the old booths by paying attention to hygienic aspects. Apart from that, the bustling market was also caused by an increase in trading commodities. The increasing number of buyers and the large number of commodities being traded are the impact of the enactment of the 1870 Agrarian Law. In its development, Pasar 16 has not only become a meeting point for traders and buyers from various social and ethnic backgrounds. More than that, there has been social interaction that has an influence, especially on the socio-economic.